Scales of Resistance : Indigenous Women's Transborder Activism. - Blackwell, Maylei (Durham : Duke University Press, 2023)
Maylei Blackwell tells the story of how Indigenous women's activism in Mexico and California moves in and between local, national, continental, and transborder scales.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books